Ionospheric variability over Indian low latitude linked with the 2009 sudden stratospheric warming. Issue 5 (27th May 2014) - Patra, A. K.; Pavan Chaitanya, P.; Sripathi, S.; Alex, S.
Abstract In this paper, we analyze radar observations of E × B drift and plasma irregularities, ionosonde observations of E and F layer parameters including spread F, and magnetic field observations made from Indian low latitudes linked with the 2009 sudden stratospheric warming (SSW) event. E × B drift variations presented here are the first of their kind from the Indian sector as far as the effect of SSW is concerned. Difference of magnetic fields observed from the equator and low‐latitude (∆H) and E × B drift show linear relation, and both show remarkably large positive values in the morning and negative values in the afternoon exhibiting semidiurnal behavior. Remarkable changing patterns in the critical frequency of F2 layer (foF2) and F3 layer (foF3) were observed after the occurrence of SSW. Large variations with quasi 16 day periodicity were observed in ∆H, foF2, and foF3. Both semidiurnal and quasi 16 day wave modulation observed after the 2009 SSW event are consistent with those reported earlier. We also noted quasi 6 day variations in ∆H and foF2 soon after the SSW commencement, not much reported before. During the counterelectrojet events linked with the SSW event, while equatorial Es (Esq) disappeared as expected, there were no blanketing Es (Esb), a finding not reported and discussed earlier. Esb was also not formed at the off‐equatorial location, indicating the absence of required vertical wind shear, but E region plasma irregularities were observed by the ionosonde and radar with a close relationship between the two. Weak F region irregularities were observed in the postmidnight hours, and case studies suggest the possible role of SSW‐related background electric field in the manifestation of postmidnight F region irregularities.